A non-enzymatic photoelectrochemical sensor based on g-C3N4@CNT heterojunction for sensitive detection of antioxidant gallic acid in food. (30th September 2022) - Li, Jiaodi; Wang, Chenxi; Chen, Xiaoling; Huang, Minghui; Fu, Qian; Li, Rongjie; Wang, Yilin; Li, Chunyan; Zhao, Pengcheng; Xie, Yixi; Fei, Junjie
Graphical abstract: Highlights: A low cost and simple method for the detection of gallic acid in food. The g-C3 N4 @CNT has good chemical stability and non-toxicity. This is a covalently bonded "signal-on" high-sensitivity non-enzyme PEC sensor. The constructed PEC sensor has an ultra-low LOD and a wide linear range. This is first PEC sensor based on g-C3 N4 @CNT heterojunction to detect gallic acid. Abstract: Gallic acid (GA) is found in a wide range of natural plants and is relevant to the health of human beings. Here, a photoelectrochemical sensing platform based on g-C3 N4 @CNT heterojunction has been prepared for the highly sensitive and selective detection of GA. Under the light of xenon lamp, the photocurrent of g-C3 N4 @CNT is 7 times higher than that of g-C3 N4 . And the sensor generates 4 times more photocurrent in the presence of GA than without GA. This sensor has a wide linear range from 10 nM to 10 μM with a limit of detection as low as 2 nM. Also, the abundant amino groups of g-C3 N4 provide excellent selectivity for the sensor. Furthermore, the sensor can be used for the analysis of GA in black tea samples, which provides a novel and rapid method for the detection of GA in food samples.